2017
DOI: 10.1007/s11356-017-9934-0
|View full text |Cite
|
Sign up to set email alerts
|

Simulations of the impacts of building height layout on air quality in natural-ventilated rooms around street canyons

Abstract: Numerical simulations were conducted to investigate the effects of building height ratio (i.e., HR, the height ratio of the upstream building to the downstream building) on the air quality in buildings beside street canyons, and both regular and staggered canyons were considered for the simulations. The results show that the building height ratio affects not only the ventilation fluxes of the rooms in the downstream building but also the pollutant concentrations around the building. The parameter, outdoor effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…Air pollution is affected by many factors, such as pollution sources, meteorological conditions [13][14][15], geographical location [16][17][18][19], human activities [20,21], and industrial production [22,23]. Some scholars developed a consumption-based emission inventory for air pollutants in the years 2007 and 2012 [24].…”
Section: Introductionmentioning
confidence: 99%
“…Air pollution is affected by many factors, such as pollution sources, meteorological conditions [13][14][15], geographical location [16][17][18][19], human activities [20,21], and industrial production [22,23]. Some scholars developed a consumption-based emission inventory for air pollutants in the years 2007 and 2012 [24].…”
Section: Introductionmentioning
confidence: 99%
“…However, lots of researchers think that ventilation capacity is the most effective method to guarantee indoor air quality (IAQ), so IAQ is strongly dependent on the environment of the street canyon [90][91][92]. Especially for buildings located in an area with serious outdoor air pollution, the coupling between indoor and outdoor air does not effectively improve IAQ but instead even aggravates indoor pollution in some cases [93].…”
Section: Relationship With Indoor Air Qualitymentioning
confidence: 99%
“…Without considering solar radiation Xie et al [18], Yang et al [19], and Hao et al [20] reported that the flow patterns are strongly related to the asymmetry aspect ratio (the ratio between the leeward and windward building heights) for 2D models. The change in flow patterns could further affect the dilution potential of in-canyon traffic-induced pollutants.…”
Section: Introductionmentioning
confidence: 99%
“…It is found that pollutant levels are raised in a step-down street canyon (higher buildings upstream) but reduced in a step-up street canyon (higher buildings downstream) in twodimensional (2D) models. Moreover, the influence of asymmetric aspect ratios (upwind building height to downwind building height) on the pollutant dispersion process was investigated by Yang et al [19] and Hao et al [20]. Yang et al [19] showed that asymmetric aspect ratios from 2/7 to 7/2 are favorable for the realization of higher air quality.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation